Design and Development of Motorised Wire loop Paddy Thresher for Hilly Region - Singh, RKP; Ghadge, S V; Satapathy, K K; Pandey, M M (Journal of Agricultural Engineering, 2003)
A light weight power operated paddy thresher with blower has been designed and developed as an improvement over pedal type paddy thresher. The machine consists of a basic frame, threshing cylinder, blower, prime mover, power transmission unit and a grain shield. Overall dimensions of the thresher are 850x750 x750 mm (lxbxh) and total weight excluding the prime mover is about 50 kg. Two persons are required to undertake the threshing operation. The threshing cylinder and prime mover can be easily detached (if necessary) from the frame to enable easy transportation of the thresher in hilly areas. The total grain output capacity is about 200 kg/hr and threshing efficiency is 98.5%. There is about 80% saving in labour requirement and 74% saving in cost of threshing operation as compared to pedal type paddy thresher.